Interactive 3D model completion - van den Hengel, A; Dick, A; Thormählen, T; Ward, B; Torr, PHS (IEEE, 2008)
A common problem when using automated structure from motion techniques is that the object to be modelled can only be partially reconstructed from the video. This can occur because not all of the object is visible in the video, or because of featureless or ambiguous regions on the object's surface. In this paper we present an interactive method for rapidly and intuitively generating a complete 3D model from the output of a structure and motion algorithm. The method combines information obtained from the video data with the partial 3D model and user interaction. It is demonstrated on video containing partially seen objects, including planar and curved surfaces, and indoor and outdoor settings. © 2007 IEEE.